Intravital methods in research into the ecology of animals and their significance in investigations on the example of Sciurus vulgaris - Julia Zizda (Праці Теріологічної школи, 2010)
Long-term and seasonal dynamics of the course and peculiarities of the epezootic process of rabies in Cherkasy Oblast in 1998–2009 are considered. A species composition of mammals involved into circulation and transmission if the virus is determined. A presumption concerning the role of cats as one of the main carriers of the virus is given; an accent at opportunity of development of “urban” type of the rabies in conditions of long-term epizootic is done.